Acúmulo de massa seca na soja em resposta a aplicação foliar com silício sob condições de déficit hídrico - Teodoro, Paulo Eduardo; Ribeiro, Larissa Pereira; Oliveira, Elisa Pereira de [UNESP]; Corrêa, Caio Cézar Guedes; Torres, Francisco Eduardo (Univ Federal Uberlandia, 2015)
The foliar fertilization with silicon has promoted several actions beneficial to plants, among them is greater drought tolerance, however, for the soybean, there is little information on these benefits in this condition. Thus, the aim of this study was to evaluate the effect of silicon on leaf, the dry matter accumulation of soybean in their reproductive stages, where the crop water stress suffered during the same. The experiment was carried out at the Plant Science Unit Aquidauana University - State University of Mato Grosso do Sul. The statistical design was a randomized block split plot with four replications. The plots were represented by cultivar 5DR615, the subplots consisted of the application (with or without) silicon, whose source was used KSi. Was measured the height and identified the development stage of all plants, separating them into stem + branches, leaves + petioles, pods capsules and seed. Foliar applications of silicon increased dry matter accumulation during the reproductive stage of soybean, where the highest values occurred in the R6 stage. Under conditions of water deficit, foliar application of silicon on soybean provided normal plant development, generating greater dry mass of stem + branches, leaves + petioles, pods capsules and seeds throughout their reproductive phase, with the highest values obtained at R6 stage (35 days after R2).

A adubação foliar com silício tem promovido diversas ações benéficas às plantas, dentre elas está a maior tolerância à deficiência hídrica, contudo, para a cultura da soja, são escassas informações destes benefícios nesta condição. Assim, objetivou-se, neste estudo, avaliar o efeito da aplicação de silício, via foliar, no acúmulo de massa seca da soja em seus estádios reprodutivos, onde a cultura sofreu deficiência hídrica durante os mesmos. O experimento foi realizado no setor de Fitotecnia da Unidade Universitária de Aquidauana - Universidade Estadual de Mato Grosso do Sul. O delineamento estatístico utilizado foi o de blocos ao acaso em parcelas subdivididas, com quatro repetições. As parcelas foram representadas pela cultivar de soja 5DR615, as subparcelas consistiram na aplicação (com e sem) de silício, cuja fonte utilizada foi o KSi. Mensurou-se a altura e identificou-se o estádio de desenvolvimento de todas as plantas, separando-as em haste + ramos, folhas + pecíolos, cápsulas de vagens e sementes, para avaliação quanto ao acúmulo de matéria seca. Em condições de déficit hídrico, a aplicação foliar de silício na soja proporcionou um desenvolvimento normal das plantas, gerando maior acúmulo de massa seca de haste + ramos, folhas + pecíolos, cápsulas de vagens e sementes durante toda sua fase reprodutiva, sendo os maiores valores obtidos no estádio R6 (35 dias após R2).
Dry mass in soybean in response to application leaf with silicon under conditions of water deficit
Keywords: Foliar fertilization; Water stress; Glycine max; Dry mass air; Adubação foliar; Estresse hídrico; Glycine max; Massa seca aérea